The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.2147/opth.s37544
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the foveal microstructure after intravitreal bevacizumab application in patients with retinal vascular disease

Abstract: PurposeTo investigate changes in the area of the foveal avascular zone (FAZ) in patients with retinal vascular disease.Patients and methodsThis retrospective, consecutive study examined 53 eyes of 53 patients with macular edema due to branch retinal vein occlusion in 25 patients (47.2%) and nonproliferative diabetic retinopathy in 28 patients (52.8%). The macular edema was treated with an intravitreal injection of 0.05 mL equal to 1.25 mg bevacizumab. Before and 6–8 weeks after the injection, best corrected vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
31
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 47 publications
2
31
0
Order By: Relevance
“…An increase in the FAZ size following intravitreal bevacizumab injections for DME has also been previously reported using FA in several noncomparative studies. 33,34 In one of these studies, there was a 19.7% increase in the FAZ area 6-8 weeks following a single bevacizumab injection for DME, 33 while another study showed a 13% increase in the FAZ area following 3 monthly bevacizumab injections which was greater in patients with milder DR. 34 This was in agreement with our results and could be due to progression of ischemia due to the underlying DR or due to VEGF inhibition or both. 34 Controlled studies are needed to further explain these findings.…”
Section: Discussionmentioning
confidence: 99%
“…An increase in the FAZ size following intravitreal bevacizumab injections for DME has also been previously reported using FA in several noncomparative studies. 33,34 In one of these studies, there was a 19.7% increase in the FAZ area 6-8 weeks following a single bevacizumab injection for DME, 33 while another study showed a 13% increase in the FAZ area following 3 monthly bevacizumab injections which was greater in patients with milder DR. 34 This was in agreement with our results and could be due to progression of ischemia due to the underlying DR or due to VEGF inhibition or both. 34 Controlled studies are needed to further explain these findings.…”
Section: Discussionmentioning
confidence: 99%
“…27,28 Further, foveal microstructure may be altered following anti-VEGF treatment in retinal vascular disease. 29 Future studies that compare treatment-naïve and previously treated eyes with RVO will help determine the effect of anti-VEGF treatment on the observed changes in the retinal microvasculature in this disease.…”
Section: Discussionmentioning
confidence: 99%
“…Measurements of the area of RNP on FA have shown that enlargement of this area is common in both BRVO and CRVO [27,28]. The mechanism is unknown, but concern has been expressed that it may be exacerbated by VEGF itself [1,19], or on the contrary from its inhibition [20,21]. For this purpose, we also analyzed the changes in the FAZ area in eyes with RVO treated with IVR in the long term.…”
Section: Discussionmentioning
confidence: 99%
“…Few reports exist on this matter in RVO, and none of them evaluated the associated long-term outcomes [17,18]. Also, some debate has been raised about the role of anti-VEGF agents in promoting retinal nonperfusion (RNP) or, on the contrary, in reducing retinal ischemia by promoting retinal reperfusion [1,19,20,21]. The impact of anti-VEGF agents in the choroid is also still poorly understood [22,23].…”
Section: Introductionmentioning
confidence: 99%